2010
DOI: 10.1126/science.1194780
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical False Memory for Objects After Brain Damage

Abstract: Poor memory after brain damage is usually considered to be a result of information being lost or rendered inaccessible. It is assumed that such memory impairment must be due to the incorrect interpretation of previously encountered information as being novel. In object recognition memory experiments with rats, we found that memory impairment can take the opposite form: a tendency to treat novel experiences as familiar. This impairment could be rescued with the use of a visual-restriction procedure that reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
187
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(214 citation statements)
references
References 25 publications
24
187
3
Order By: Relevance
“…The observation that top-down feedback from PRC suppressed part-based responses in lower-level visual regions is consistent with a recent series of findings suggesting that the PRC may be critical in resolving perceptual interference (McTighe et al, 2010;Burke et al, 2010;Romberg et al, 2012;Barense et al, 2012;Newsome et al, 2012). For example, patients with PRC damage were impaired at perceptual discrimination under conditions of high visual interference (a series of complex object discriminations for which object parts were repeatedly presented across trials), but performed normally under conditions of low visual interference (fewer object parts repeated across trials) Newsome et al, 2012).…”
Section: Visual Cortex Activationsupporting
confidence: 75%
See 1 more Smart Citation
“…The observation that top-down feedback from PRC suppressed part-based responses in lower-level visual regions is consistent with a recent series of findings suggesting that the PRC may be critical in resolving perceptual interference (McTighe et al, 2010;Burke et al, 2010;Romberg et al, 2012;Barense et al, 2012;Newsome et al, 2012). For example, patients with PRC damage were impaired at perceptual discrimination under conditions of high visual interference (a series of complex object discriminations for which object parts were repeatedly presented across trials), but performed normally under conditions of low visual interference (fewer object parts repeated across trials) Newsome et al, 2012).…”
Section: Visual Cortex Activationsupporting
confidence: 75%
“…As a result of this interaction familiarity/novelty responses in lower-level visual regions and higherlevel MTL regions are coordinated to drive a coherent behavioral response. This feedback interpretation builds on evidence that the PRC discriminates between novel and familiar objects (Xiang and Brown, 1998;Henson et al, 2003;Kohler et al, 2005;Albasser et al, 2010;Burke et al, 2010;McTighe et al, 2010). The feedback framework explains why effects of part familiarity cannot be observed independently of effects of configuration familiarity in behavioral tasks conducted with nonbrain-damaged participants: when the PRC is intact, part familiarity responses at lower-levels are suppressed when familiar parts appear in Part-Rearranged Novel Configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Lesions of the perirhinal cortex have been shown to impair performance in the object recognition task (Ennaceur et al, 1996;) and more recent work has shown that the perirhinal cortex is required for the encoding, consolidation and retrieval of object recognition memory (Winters and Bussey, 2005a,b;Winters et al, 2008). Yet, recently it has been suggested that perirhinal lesions do not impair memory formation but may instead cause the occurrence of false memories; rats with perirhinal cortex lesions show a number of false positive hits on a modified version of the object recognition task as they treated novel objects as familiar (McTighe et al, 2010). McTighe et al (2010) also demonstrated that this false memory was due to interference between the training and testing phases of the task; putting the rats in a visually restrictive environment restored the perirhinal cortex lesioned rats to the same levels of object exploration as the controls.…”
Section: Object Recognition Memorymentioning
confidence: 99%
“…Yet, recently it has been suggested that perirhinal lesions do not impair memory formation but may instead cause the occurrence of false memories; rats with perirhinal cortex lesions show a number of false positive hits on a modified version of the object recognition task as they treated novel objects as familiar (McTighe et al, 2010). McTighe et al (2010) also demonstrated that this false memory was due to interference between the training and testing phases of the task; putting the rats in a visually restrictive environment restored the perirhinal cortex lesioned rats to the same levels of object exploration as the controls.…”
Section: Object Recognition Memorymentioning
confidence: 99%
“…Research has revealed a central role for the perirhinal cortex (PRh) in object representation (Buckley and Gaffan, 2006;Barker et al, 2007;Bartko et al, 2007;Bussey and Saksida, 2007;McTighe et al, 2010). Indeed, studies with the spontaneous object recognition (SOR) task for rats have implicated PRh in object memory encoding, consolidation, and retrieval (Winters and Bussey, 2005a,b;Barker et al, 2006a,b).…”
Section: Introductionmentioning
confidence: 99%